2017
DOI: 10.3906/fiz-1703-10
|View full text |Cite
|
Sign up to set email alerts
|

Second law of gravitational thermodynamics in the locally rotationally symmetric Bianchi type-II universe

Abstract: Abstract:In this work, under the assumption that the universe is locally rotationally symmetric (LRS) Bianchi type-II and filled with anisotropic dark fluid (dark energy and dark radiation), we investigate whether the generalized second law of thermodynamics (GSLT) is still valid. We also consider another important condition for LRS Bianchi type-II spacetimes whereby the model expansion θ is proportional to the shear σ , which leads to B = A n (where n is a constant and A and B are the metric potentials). Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Accordingly, from a thermodynamic point of view, Jacobson first showed that the equation of state of space-time is exactly the standard Einstein equations. This is a significant step because determining the relationship between thermodynamics and gravity has made it easier to consider the concept of dark a e-mails: aliihsan.keskin@batman.edu.tr; alikeskin039@gmail.com (corresponding author) b e-mail: kadri.kurt@batman.edu.tr energy from a thermodynamic perspective [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In this direction, cosmic spacetime, as a whole, can be considered a thermodynamics system to study the second law of thermodynamics (cosmological entropy law).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, from a thermodynamic point of view, Jacobson first showed that the equation of state of space-time is exactly the standard Einstein equations. This is a significant step because determining the relationship between thermodynamics and gravity has made it easier to consider the concept of dark a e-mails: aliihsan.keskin@batman.edu.tr; alikeskin039@gmail.com (corresponding author) b e-mail: kadri.kurt@batman.edu.tr energy from a thermodynamic perspective [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In this direction, cosmic spacetime, as a whole, can be considered a thermodynamics system to study the second law of thermodynamics (cosmological entropy law).…”
Section: Introductionmentioning
confidence: 99%